East Asian low marriage and birth rates: The role of life history strategy, culture, and social status affordance. (15th April 2019) - Yong, Jose C.; Li, Norman P.; Jonason, Peter K.; Tan, Yi Wen
Abstract: Although economic development is broadly associated with low fertility, countries with a predominantly East Asian cultural population exhibit the lowest fertility rates in the developed world. This study ( N  = 243) examined social status affordance (SSA) as a novel factor underlying cultural variations in marriage and childbearing attitudes. Drawing from a life history perspective, we argue that SSA reflects the availability and ease of attaining social status from the environment, which then influences people's reproductive motivations. We found that strong competition for prestigious jobs in developed East Asian countries, which is hypothesized to be an outcome of their collectivistic nature and the importance they place on endowed social status, was associated with reduced SSA and, in turn, less favorable attitudes towards marriage and preference for less children. These effects were driven by men, primarily. We conclude with a discussion of the implications and suggestions for further research.